The feasibility of a pragmatic distance‐based intervention to increase physical activity in lung cancer survivors. (9th June 2017) - Peddle‐McIntyre, C.J.; Baker, M.K.; Lee, Y.C.G.; Galvão, D.A.; Cormie, P.; Graham, V.; Newton, R.U.
Abstract : The purpose of this study was to investigate the feasibility and preliminary efficacy of a pragmatic distance‐based intervention designed to increase physical activity (PA) participation in lung cancer survivors. Fourteen lung cancer survivors were recruited via invitation from the State Cancer Registry to join a 12‐week PA intervention of print materials paired with brief telephone follow‐up. Outcome measures of feasibility, PA participation and quality of life (QoL) were assessed at baseline, post‐intervention and follow‐up via telephone interview. Eligibility, recruitment and attrition rates were 16%, 58% and 29% respectively. No adverse events were reported; however, pain scores worsened following the intervention (median change −3.6, IQR −8.0, 0.0). Average intervention adherence was 91% with low median ratings of participation burden (i.e., all items 1/7) and high trial evaluation (i.e., all items 7/7). Post‐intervention, median change in self‐reported moderate and vigorous PA was 84 min (IQR −22, 188), and several domains of QoL improved. However, for both of these outcomes, improvements were not maintained at follow‐up. Our findings suggest that this pragmatic distance‐based intervention was safe, had good adherence rates, and indicate potential for improving short‐term PA and QoL in lung cancer survivors. Additional strategies are needed to improve other indicators of feasibility, particularly recruitment, retention and long‐term maintenance of improvements. Australian New Zealand Clinical Trials Registration: ACTRN12612000085875.